Strategi Pemasaran Melalui Google Bisnisku Dengan SEO Untuk Meningkatkan Penjualan Spandek - Widiawati, Kristiana; Yuliani, Tri (JURNAL ADMINISTRASI KANTOR; Vol 10 No 2 (2022): Jurnal Administrasi Kantor (Desember 2022), 2023)
In facing this intense competition, companies need the right, targeted, and well-planned strategy that can maintain the company's position. Companies also need to choose tools that sell services in boosting the company's popularity.The purpose of this study was to determine the effect of digital marketing carried out on CV Patriot Baja Mas on increasing sales. The problems experienced by CV Patriot Baja Mas before choosing digital marketing in its marketing strategy have done conventional promotions such as self-introduction and products sold from store to store, direct marketing and others but the results obtained are still not optimal. The solution used to solve these problems is the need for a marketing strategy that is able to increase sales of spandek products at CV Patriot Baja Mas more significantly by using digital marketing marketing strategies. In this study using qualitative methods with data collection techniques in the form of interviews and observations. The results of the study state that the application of digital marketing that incorporates the role of SEO has a significant effect on increasing sales of CV Patriot Baja Mas spandex products by using the Google My Business product proposal. With Google My Business, it can be directly integrated with Google Maps, making it easier for potential customers to find the company's location.     Keywords : Digital marketing, SEO, Google My Business.